POTENSI TO’TOAN (TACCA LEONTOPETALOIDES (L.) O.KUNTZE) SEBAGAI BAHAN PANGAN DI PULAU KANGEAN, JAWA TIMUR - Susiarti, Siti (BERITA BIOLOGI, 2015)
Tacca leontopetaloides (L.) O. Kuntze has the potential as food alternative source from its tubers and therefore selected for food diversification study.This research was conducted on Kangean island using open-ended interview methods,field observations,purposive sampling and chemical analysis.Tacca leontopetaloides still not much known and utilizated by the local people in East Java.The plant has different local names for each region, such as in Madura they known as "lorkong" and "oto'o", while in Kangean island,known as "to?toan". In Kangean island, local people utilized the tuber to make flour using simple process. The flour was used as a substitute for wheat flour mainly as an ingredient for porridge, cakes ?serpot? and ?eped-eped (omelette)?. The species was generally grow wild in teak garden, so they can be used as an alternative crop under the teak stands. Proximate analysis of Tacca leontopetaloides tubers was also carried out and showed that they contained: 2.67 ? 2.71 % of ash; 6.73 - 7.84 % of protein; 0.43 ? 1.90 % of fat; 0.41 - 0.60 % of crude fibre; 77.09 - 82.65 % of carbohydrate and available energy 352.36 - 365.83 Kcal/100g based on dry weight. Mineral content was also analysed and showed the following value: 173.50 - 173.67 mg/100g of magnesium; 4.00 - 8.69 mg/100g of iron; 69.89 - 87.72 mg/100g of calsium; 904.86 - 966.74 mg/100g of potassium; and 222.59 - 270.46 mg/100g of phosphor. Hence, Tacca leontopetaloides has sufficient nutrient contents from its carbohydrate and mineral.